Hospital Tweets on H1N1 and Death Panels: Text Mining the Situational Crisis Communication Response to Health Crises and Controversies - Aimee Kendall Roundtree (KOME: An International Journal of Pure Communication Inquiry)
This thematic and text mining analysis interrogates hospital tweets about H1N1 flu and healthcare reform in 2009 using the situational crisis communication theory (SCCT) and manufactured controversies, or casting doubt on scientific and medical consensus to delay or thwart public policy. Hospitals minimally responded to both issues and situated themselves as neutral, ambivalent agents separate from the government and skeptics. Tweets that recycled links to news sources inherited limitations that plagued media coverage in their incapacity for quick response. To handle controversies, an adapted SCCT might require more direct and dialogic strategies, as well as defensive and offensive tactics, such as increasing hosted events, outreach, and statements of expert opinion